Microhabitat Variability in Human Evolution - Patalano, Robert; Hamilton, Rebecca; Finestone, Emma; Amano, Noel; Heddell-Stevens, Phoebe; Itambu, Makarius; Petraglia, Michael; Roberts, Patrick (Frontiers in Earth Science, 2021)
Climate variability and hominin evolution are inextricably linked. Yet, hypotheses examining the impact of large-scale climate shifts on hominin landscape ecology are often constrained by proxy data coming from off-site lake and ocean cores and temporal offsets between paleoenvironmental and archaeological records. Additionally, landscape response data (most commonly, records of vegetation change), are often used as a climate proxy. This is problematic as it assumes that vegetation change signifies global or regional climate shifts without accounting for the known non-linear behavior of ecological systems and the often-significant spatial heterogeneity in habitat structure and response. The exploitation of diverse, rapidly changing habitats by Homo by at least two million years ago highlights that the ability to adapt to landscapes in flux had emerged by the time of our genus’ African origin. To understand ecosystem response to climate variability, and hominin adaptations to environmental complexity and ecological diversity, we need cross-disciplinary datasets in direct association with stratified archaeological and fossil assemblages at a variety of temporal and spatial scales. In this article, we propose a microhabitat variability framework for understanding Homo’s adaptability to fluctuating climates, environments, and resource bases. We argue that the exploitation of microhabitats, or unique ecologically and geographically defined areas within larger habitats and ecoregions, was a key skill that allowed Homo to adapt to multiple climates zones and ecoregions within and beyond Africa throughout the Pleistocene.